Towards self-organising global supply chains in the internet of things - CLARKE, SIOBHAN; CUNNINGHAM, RAYMOND; SENART, ALINE; CAHILL, VINNY (IEEE, 2007)
Current supply chain management software architectures, although distributed, typically put decision making and con- trol at the centre of the network. Such architectures do not scale well with increasing complexity, dynamism and volume of available business information from the so-called ?Internet of things?. In this paper, we investigate highly de- centralised and self-organising middleware architectures for global supply chain management. We propose to model sup- ply chains as collections of cooperating/competing agents that represent smart artefacts, services, and/or business pro- cesses. We outline the key requirements to be addressed in order to support this decentralised self-organising network of agents governed by high-level policy specifications.
International Workshop on System Support for the Internet of Things : 1st : 2007
PUBLISHED
Keywords: Self-organisation; decentralised supply chains; optimisation; service bus